Arsenic and cation metal removal from copper slag using a bipolar membrane electrodialysis system. (1st March 2022) - Liu, Yaoxing; Dai, Liping; Ke, Xiong; Ding, Jianguo; Wu, Xiaoyun; Chen, Riyao; Ding, Rui; Van der Bruggen, Bart
Abstract: A three-step bipolar membrane electrodialysis (BMED) system was used to remove arsenic and cation metals from copper slag (CS) generated during the copper ore hydrometallurgical process. The desorption kinetics results show that pH significantly influences metal desorption from CS. The Elovich model can be used to describe metal desorption. A high current density increased the metal desorption from CS into the supernatant. Metal removal also increased with current density when the BMED system was used for supernatant treatment. Increasing the number of supernatant compartments from one to two and three increased the current efficiency from 38.0% to 75.3% and 112.3%, respectively; the specific energy consumption decreased from 0.051 to 0.035 kWh/g and 0.029 kWh/g of metal removal, respectively. The supernatant (pH = 0.77) could be used as the leaching solution for leaching copper from raw copper ore during the copper ore hydrometallurgical process without discharging wastewater. During the treatment process, 79.6% of AsO4 3− could be recovered in the form of H3 AsO4 . The metal removal rates for arsenic, calcium, cadmium, cobalt, chromium, copper, iron, magnesium, nickel and zinc were 96.5%, 22.8%, 75.8%, 54.8%, 49.5%, 59.5%, 71.1%, 65.5%, 48.5% and 83.0%, respectively. Only a small amount of state-stabilised residual state metals remained in the CS, thereby realising the objective of recovering arsenic and removing cation metals. The present method was found to be an efficient and green technique for removing metals from CS and other solid waste materials contaminated with heavy metals. Graphical abstract: Image 1 Highlights: A three-step bipolar membrane electrodialysis system was fabricated. Recovery of arsenic and removal of cation metals from copper slag was investigated. More than 79.6% of arsenic can be recovered in form of H3 AsO4 . Metal remained in treated CS was main stablilised residual state. No wastewater was discharged during the whole treatment process.